PROMOTING LEARNERS’ AUTONOMY THROUGH VIDEO RECORDING IN PUBLIC SPEAKING CLASS - Deva Melania; Wiwiet Eva Savitri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The change in the learning system from the previous teacher-centeredness to learner-centeredness makes the students demand to take responsibility, manage learning, and implement knowledge to become autonomous learners, especially in speaking class. However, in learning to speak, teachers dominate most learning activities, making students passive to take their responsibilities. Because of this problem, teachers must be innovative and engage students in interactive learning activities to make them active by using technology. One of the ways is through video recording. Previous studies claimed that students who used video recording in speaking class improved their speaking competencies and self-confidence. Nevertheless, previous studies mainly focused on students’ speaking competence rather than learner autonomy. Hence, this study aims to investigate learner autonomy in speaking class with video recording. The participants of this study were an English lecturer and students taking a Public Speaking Class at one university in Surabaya. During a series of data collection activities, the researcher observed how the lecturer introduced video recording implementation and did the interview to know how the students implemented their autonomy in learning speaking through video recording. The result showed that the lecturer was active in encouraging students to develop their learning responsibility and independence by implementing reactive autonomy. As a result, students delivered speeches on video recording through the learner autonomy stages properly